Atypical presentation of purpura fulminans following sepsis in an adult. (28th October 2011) - Lyon, Paul; Nambi, Rabi; Faruqi, Faisal
Abstract : A 67-year-old morbidly obese female with a background of stage 4 chronic renal failure, ischaemic heart disease, congestive cardiac failure, atrial fibrillation and type 2 diabetes mellitus presented with sepsis and necrotic lesions of the proximal lower limbs. Initial histological findings were consistent with the clinical diagnosis of calciphylaxis and supportive treatment was commenced with addition of a phosphate binder and dietary restriction. Due to high anaesthetic risk, her wounds were managed with larva therapy in the first instance, however, ultimately surgical debridement was the required. Repeat histology from a further biopsy revealed necrosis secondary to numerous thrombi in the cutaneous vessels and a new diagnosis of purpura fulminans was made, likely secondary to her sepsis. Unfortunately, despite aggressive medical and surgical treatment measures, this patient died of multiple organ dysfunction following a prolonged admission.